Cellular Tight Junctions Prevent Effective Campylobacter jejuni Invasion and Inflammatory Barrier Disruption Promoting Bacterial Invasion from Lateral Membrane in Polarized Intestinal Epithelial Cells - Hatayama, Sho; Shimohata, Takaaki; Amano, Sachie; Kido, Junko; Nguyen, Anh Q.; Sato, Yuri; Kanda, Yuna; Tentaku, Aya; Fukushima, Shiho; Nakahashi, Mutsumi; Uebanso, Takashi; Mawatari, Kazuaki; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Campylobacter jejuni invasion is closely related to C. jejuni pathogenicity. The intestinal epithelium contains polarized epithelial cells that form tight junctions (TJs) to provide a physical barrier against bacterial invasion. Previous studies indicated that C. jejuni invasion of non-polarized cells involves several cellular features, including lipid rafts. However, the dynamics of C. jejuni invasion of polarized epithelial cells are not fully understood. Here we investigated the interaction between C. jejuni invasion and TJ formation to characterize the mechanism of C. jejuni invasion in polarized epithelial cells. In contrast to non-polarized epithelial cells, C. jejuni invasion was not affected by depletion of lipid rafts in polarized epithelial cells. However, depletion of lipid rafts significantly decreased C. jejuni invasion in TJ disrupted cells or basolateral infection and repair of cellular TJs suppressed lipid raft-mediated C. jejuni invasion in polarized epithelial cells. In addition, pro-inflammatory cytokine, TNF-α treatment that induce TJ disruption promote C. jejuni invasion and lipid rafts depletion significantly reduced C. jejuni invasion in TNF-α treated cells. These data demonstrated that TJs prevent C. jejuni invasion from the lateral side of epithelial cells, where they play a main part in bacterial invasion and suggest that C. jejuni invasion could be increased in inflammatory condition. Therefore, maintenance of TJs integrity should be considered important in the development of novel therapies for C. jejuni infection.